Advanced sports nutrition. - Benardot, Dan, ....- (Champaign : Human Kinetics, 2012)
Advanced Sports Nutrition helped thousands of athletes apply the most effective and cutting-edge strategies for optimal fueling and performance. Now this best-seller returns, updated with the latest research, topics, and innovations in sports nutrition. Far beyond the typical food pyramid formula, Advanced Sports Nutrition offers serious strategies for serious athletes. This comprehensive guide includes the latest nutrition concepts for athletes in any sport. World-renowned sports nutritionist Dr. Dan Benardot breaks down the chemistry of improved performance into winning principles that ensure athletes' key energy systems are properly stocked at all times: - Meal, energy, and nutrient timing guidelines to maintain that crucial energy balance throughout the day - Optimal ratios and quantities of nutrients, vitamins, and minerals for any sport - Guidelines on indentifying and maintaining optimal body composition for maximal power, strength, and athletic performance - The latest research on ergogenic aids, such as quercitin and caffeine - Strategies for avoiding gastrointestinal distress during activity and reducing exercise-induced inflammation - The effects of travel, high altitude, and age on nutrition needs and performance - Strategies for balancing fluid and electrolytes to avoid dehydration and hyperhydration - Sport-specific guidelines for increased power, strength, and endurance The best conditioning programs and technical instruction are beneficial only if your body is properly fueled and ready to operate at peak efficiency. With Advanced Sports Nutrition, Second Edition, you can be assured that when you are ready to push the limits of training and competition, your body is, too. Contents Part I Nutrition Sources for Athletes
Chapter 1. Energy Nutrients Chapter 2. Vitamins and Minerals Chapter 3. Fluids and Electrolytes Chapter 4. Ergogenic Aids Part II Nutrition Aspects of Optimal Performance Chapter 5. G-I Function and Energy Delivery Chapter 6. Nutrient and Fluid Timing Chapter 7. Oxygen Transportation and Utilization Chapter 8. Strategies for Anti-Inflammation and Muscular Health Part III Factors Affecting Nutrition Needs Chapter 9. Travel Chapter 10. High Altitude Chapter 11. Gender and Age Chapter 12. Body Composition and Weight Part IV Nutrition Strategies for Specific Energy Systems Chapter 13. Anaerobic Metabolism for High-Intensity Bursts and Power Chapter 14. Aerobic Metabolism for Endurance Chapter 15. Metabolic Needs for Both Power and Endurance Part V Nutrition Plans for Specific Sports Chapter 16. Sports Requiring Power and Speed Chapter 17. Sports Requiring Endurance Chapter 18. Sports Requiring Combined Power and Endurance
Keywords: Sport en voeding